VIA/VILI is more suitable for cervical cancer prevention in Chinese poverty-stricken region: a health economic evaluation - Yu Xie; Xiaodong Tan; Haiyan Shao; Qing Liu; Jiyu Tou; Yuling Zhang; Qiong Luo; Qunying Xiang (BMC, 2017)
Abstract Background Screening is the main preventive method for cervical cancer in developing countries, but each type of screening has advantages and disadvantages. To investigate the most suitable method for low-income areas in China, we conducted a health economic analysis comparing three methods: visual inspection with acetic acid and Lugol's iodine (VIA/VILI), ThinPrep cytology test (TCT), and human papillomavirus (HPV) test. Methods We recruited 3086 women aged 35-65 years using cluster random sampling. Each participant was randomly assigned to one of three cervical cancer screening groups: VIA/VILI, TCT, or HPV test. In order to calculate the number of disability-adjusted life years (DALYs) averted by each screening method, we used Markov models to estimate the natural development of cervical cancer over a 15-year period to estimate the age of onset and duration of each disease stage. The cost-effectiveness ratios (CERs), net present values (NPVs), benefit-cost ratios (BCRs), and cost-utility ratios (CURs) were used as outcomes in the health economic analysis. Results The positive detection rate in the VIA/VILI group was 1.39%, which was 4.6 and 2.0 times higher than the rates in the TCT and HPV test groups, respectively. The positive predictive value of VIA/VILI (10.53%) was highest while the rate of referral for colposcopy was lowest for those in the HPV + TCT group (0.60%). VIA/VILI performed the best in terms of health economic evaluation results, as the cost of per positive case detected was 8467.9 RMB, which was 24503.0 RMB lower than that for TCT and 5755.9 RMB lower than that for the HPV test. In addition, the NPV and BCR values were 258011.5 RMB and 3.18 (the highest), and the CUR was 2341.8 RMB (the lowest). The TCT performed the worst, since its NPV was <0 and the BCR was <1, indicative of being poorly cost-beneficial. Conclusions With the best economic evaluation results and requiring minimum medical resources, VIA/VILI is recommended for cervical cancer screening in poverty-stricken areas in China with high incidence of cervical cancer and lack of medical resources.